CHARACTER EDUCATION DURING THE COVID-19 PANDEMIC AT SMA MUHAMMADIYAH 1 SURAKARTA - Elly Elliyun; Sutama Sutama; Ahmad Muhibbin (Jurnal Scientia, 2023)
The study aimed to describe the implementation of character education during the covid-19 pandemic at SMA Muhammadiyah 1 Surakarta and the problems of character education during the covid-19 pandemic at SMA Muhammadiyah 1 Surakarta and to describe solutions to character education problems during the covid-19 pandemic at SMA Muhammadiyah 1 Surakarta. Qualitative descriptive research involves participating in observation techniques, in-depth interviews, and literature study. The research location was at SMA Muhammadiyah 1 Surakarta with school principal, teachers, and students as informants. The results showed that character education during the Covid-19 pandemic at SMA Muhammadiyah 1 Surakarta was blended learning through intra-curricular, co-curricular and extra-curricular activities. Implementation of character education in blended learning is a challenge and problem in itself, especially SMA Muhammadiyah 1 Surakarta as a stage 1 The Mobilization School Program has to use the Merdeka Curriculum for class X and XI students, while class XII uses the 2013 curriculum. These problems can be overcome with various strategies including synergy with various related parties and empowering school human resources.